Job Satisfaction in the Hospitality Industry Focus: Greece Case Study: Porto Carras Grand Resort - Salpisti, Elisavet (2004)
This dissertation focuses on the notion of Job Satisfaction in the Hospitality Industry. The organisational single-case study has been chosen as a research method, with research taking place in Porto Carras Grand Resort in Northern Greece. The purpose of this research has been to demonstrate the importance of employee job satisfaction in the hospitality industry in particular, since the quality of its services is greatly subject to the 'human chemistry' between employees and customers. Job Satisfaction has been placed in the wider context of a proper Human Resource Discipline that organisations of this type need to adopt because of the distinct nature of the 'product' (service) offering. Such organisations need to seek their competitive advantage in their people. To be able to achieve this, managers have to properly motivate their employees, with Job Satisfaction being the centre of attention since as theory suggests and as this research also supports, this is an element that influences very important organisational aspects such as: employee commitment and loyalty to the organisation, turnover, performance and finally, customer satisfaction. Job Satisfaction is not an easily defined concept and the use of motivational theory aims at offering insights to its different aspects.